Price book of the Columbia Cabinet Makers' Society, Washington, D.C. - Columbia Cabinet Makers' Society (Washington, D.C.)
Price book (82 pages) containing prices recommended for furniture made by journeyman cabinetmakers in Washington, D.C.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cabinetmakers -- Societies, etc. -- Washington (D.C.); Furniture -- Prices